Alternatif Pendidikan Non Formal dalam Meningkatkan Akhlak pada Anak Melalui Pendidikan Berbasis Masjid (Madrasah Diniyah/Sekolah Agama) - Eddy Saputra (Universitas Indraprasta PGRI Jakarta, 2019)
Changes in behavior are one of the goals of the education process. Behavior in Islam is called Akhlaq. Akhlaq in Indonesian is called character, where human behavior can be formed through the process of education in order to become a better person. Not only formal-based education there is also non-formal education and this is usually often held in mosques. Besides being used as a place of worship, a mosque can also be used as a place of religious study, the aim of which is to provide an understanding of Islamic values that are minimal in formal schools. The purpose of religious knowledge is conveyed to make children have a good personality that is akhlakul karimah. The morals of children are fostered and enhanced through mosque-based education where the material is about religion taught in the mosque. This writing uses qualitative research, because research is based on field observations. The purpose of writing is making children want to learn the science of religion which is held in a regular mosque. This kind of education is usually called Madrasah Diniyah or religious school.